Engineering homoaromatic substrate specificity into aliphatic-specific Geobacillus pallidus RAPc8 nitrile hydratase - Kowlessur, Parikshant (University of the Western Cape, 2013)
Magister Scientiae - MSc === Geobacillus pallidus RAPc8 is a thermophilic nitrile-degrading isolate, obtained from thermal sediment samples of a New Zealand hot spring. The G. pallidus RAPc8 NHase gene has been cloned and expressed in E. coli. The recombinant NHase exhibits nitrile-degrading activity at 50 °C, capable of degrading branched, linear and cyclic heteroaromatic nitrile substrates. However, no activity was found on homoaromatic nitrile substrates such as benzonitrile. In the present study, high levels of activity on benzonitrile were detected with a double mutant βF52GβF55L. Kinetic analysis on the mutant enzyme showed an 8-fold decrease in KM with benzonitrile (0.3mM) compared to acrylonitrile (2.6mM). Specificity constants (kcat/KM) of 5900 and 450 s-1.mM-1 were obtained for the double mutant on benzonitrile and acrylonitrile respectively. The amino acid residues lining the substrate channel were identified and the geometric dimensions measured. Cavity calculations revealed a 29% increase in volume and a 13% increase in inner surface area for the substrate channel of the double mutant when compared to the wild type. Surface representation of the wild type structure revealed two extended, curved channels, which are accessible to the bulk solvent from two locations in the heterodimer. The removal of the βF52may have contributed to the presence of a single channel with two opposing openings across the dimers with no internal blockage. Normal Mode Analysis calculations also indicate a higher intrinsic flexibility of the mutant relative tothe wild type enzyme. The increased flexibility within the mutant NHase could have introduced a functionally relevant aromatic substrate recognition conformation. === South Africa